RESULTS OF POPULATION SURVEY ON HEALTHY LIFESTYLE - Sattarovna, Avezova Guloyim; Ugli, Abdupattaev Zukhriddin Abdulaziz; Sattarovna, Avezova Gulshod (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY RESEARCH AND INNOVATIVE TECHNOLOGIES, 2021)
A healthy lifestyle is a concept of human activity aimed at improving and maintaining health through proper nutrition, physical fitness, morale and rejection of bad habits. Thus, the data obtained show that the older age group values health more than young people. Pensioners who have acquired their own individual experience of destroying and restoring health perceive it as the greatest value in life, which is typical of the older generation, regardless of social origin.